Ink & sigil - Hearne, Kevin ([Ink & sigil], 2020)
"New York Times bestselling author Kevin Hearne returns to the world of his beloved Iron Druid Chronicles in a spin-off series about an eccentric master of rare magic solving an uncanny mystery in Scotland. Al MacBharrais is both blessed and cursed. He is blessed with an extraordinary white moustache, an appreciation for craft cocktails-and a most unique magical talent. He can cast spells with magically enchanted ink and he uses his gifts to protect our world from rogue minions of various pantheons, especially the Fae. But he is also cursed. Anyone who hears his voice will begin to feel an inexplicable hatred for Al, so he can only communicate through the written word or speech apps. And his apprentices keep dying in peculiar freak accidents. As his personal life crumbles around him, he devotes his life to his work, all the while trying to crack the secret of his curse. But when his latest apprentice, Gordie, turns up dead in his Glasgow flat, Al discovers evidence that Gordie was living a secret life of crime. Now Al is forced to play detective-while avoiding actual detectives who are wondering why death seems to always follow Al. Investigating his apprentice's death will take him through Scotland's magical underworld, and he'll need the help of a mischievous hobgoblin if he's to survive"--